Wear Mechanism of Superhard Tetrahedral Amorphous Carbon (ta‐C) Coatings for Biomedical Applications. Issue 7 (22nd January 2023) - Rothammer, Benedict; Schwendner, Michael; Bartz, Marcel; Wartzack, Sandro; Böhm, Thomas; Krauß, Sebastian; Merle, Benoit; Schroeder, Stefan; Uhler, Maximilian; Kretzer, Jan Philippe; Weihnacht, Volker; Marian, Max
Abstract: Tetrahedral amorphous carbon (ta‐C) coatings have the potential to protect biomedical implants from wear and increase their service life. This study elucidates the biocompatibility, mechanical properties, adhesion, and wear resistance of ta‐C coatings fabricated by physical vapor deposition on cobalt‐chromium‐molybdenum (CoCr) and titanium (Ti64) alloys as well as ultrahigh molecular weight polyethylene (UHMWPE). Satisfactory cytocompatibility is verified using contact angle and surface tension measurements as well as indirect and direct cell testing. Scratch testing demonstrates excellent adhesion to the substrates and as confirmed by nanoindentation, the coatings represent an up to 13‐fold and 182‐fold increase in hardness on the hard and soft materials. In metal pin‐on‐UHMWPE disk sliding experiments under simulated body fluid lubrication, the wear rates of the disk are reduced by 48% (against CoCr) and 73% (against Ti64) while the pin wear rates are reduced by factors of 20 (CoCr) and 116 (Ti64) compared to uncoated pairings. From optical and laser scanning microscopy, Raman measurements, and particle analyses, it is shown that the underlying substrates remain well protected. Nonetheless, focused ion beam scanning electron microscopy revealed coating process‐related and thermally driven subductions as well as tribologically induced near‐surface fatigue, which can potentially constitute critical wear mechanisms. Abstract : Tetrahedral amorphous carbon (ta‐C) coatings have the potential to protect load‐bearing biomedical implants from wear and thus increase their service life. This study, therefore, elucidates the biocompatibility, mechanical properties, adhesion, and wear mechanisms of ta‐C coatings fabricated by physical vapor deposition on cobalt‐chromium‐molybdenum and titanium alloys as well as ultra‐high‐molecular‐weight polyethylene implant materials.